Solid Components of Welding Fumes as a Synthetic Composites Filler; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Grishagin V. M. Viktor Mikhailovich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen